Supercoiling of DNA and nuclear conformation during the cell-cycle. - Warren, A; Cook, P (1978)
When cells are lysed in solutions containing high concentrations of salt and a non-ionic detergent, structures are released which retain many of the morphological features of nuclei. These nucleoids contain superhelical DNA but are depleted of nuclear protein. We have analysed DNA conformation in nucleoids derived from HeLa cells synchronized at different stages in the cell cycle. The gross differences in nuclear morphology seen during the cell cycle are reflected in the morphology of the nucleoids; for example, the individual chromosomes of mitotic cells remain identifiable and aggregated within the mitotic nucleoid. The sedimentation rate of nucleoids in sucrose gradients reflects the gross nuclear morphology; the small S-phase nucleoids sediment 9 times faster than the large mitotic nucleoids. Despite these large differences at the gross level of organization, both the degree of supercoiling and the size of the units in which supercoiling is maintained are roughly similar in the nucleoids derived from cells in the different phases. The protein content of the various nucleoids is also very similar. Like the nucleoids made from randomly growing cultures of cells, mitotic nucleoids are excellent templates for the RNA polymerase of Escherichia coli.